Molecular Workbench; The Curious Wavefunction; B.R.S.M.: - Cañari Chumpitaz, Cristhian (2013)
Molecular Workbench(http://mw.concord.org/modeler/)The Curious Wavefunction (http://blogs.scientificamerican.com/the-curious-wavefunction/)B.R.S.M. (http://brsmblog.com/)